Protection of calves against Haemonchus placei and Haemonchus contortus after immunization with gut membrane proteins from H. contortus - Bassetto, C. C. [UNESP]; Silva, B. F. [UNESP]; Newlands, G. F. J.; Smith, W. D.; Amarante, Alessandro Francisco Talamini do [UNESP] (Wiley-Blackwell, 2011)
A vaccine containing integral membrane glycoproteins from the intestine of Haemonchus contortus was evaluated in four groups of nine worm-free calves challenged with either 8000 H. contortus or Haemonchus placei infective larvae. Vaccinates received 50 mu g of the antigen and 1 mg QuilA adjuvant three times 21 days apart, while the controls got adjuvant alone. The calves were challenged 7 days after the last immunization and killed for worm counts 43 days later. Immunization resulted in high titre antibodies against the vaccine antigens and significant reduction in egg output and worm numbers of both challenge species, compared with control calves. It was concluded that vaccination of calves with native parasite gut membrane glycoproteins obtained from H. contortus conferred protection against both H. placei and H. contortus.
Keywords: cattle; Haemonchus contortus; Haemonchus placei; parasitic gastroenteritis; vaccine